To find the missing exponent in the equation, we can use the quotient rule of exponents:
a^m/a^n = a^(m-n)
In this case, we have:
3^E / 3^65 = 3^e / 3^38.
To find the missing exponent E, we can set up an equation using the quotient rule:
3^(E-65) = 3^(e-38).
Since the bases (3) are the same, the exponents must be equal. Therefore, we have:
E - 65 = e - 38.
To solve for E, we can rearrange the equation:
E = e - 38 + 65.
Simplifying further:
E = e + 27.
Quotient Rule of Exponents
What is the missing exponent in the following equation?
3
E?/e65 = e/38
1 answer